(untitled) (FULafia Journal of Science and Technology, 2020)
Due to the myriad complexities in medical diagnoses, there is therefore the need to develop Expert systems that will help ameliorate decision making in confusable diseases scenarios. Diagnosis has become a difficult procedure in healthcare management due to the influence of therapeutic uncertainties that arise from confusion in disease symptoms that occur between two or more diseases. This confusion stems from the overlaps in the disease symptomatic presentation and has led to improper diagnosis with various degrees of associated costs and in worst scenarios has led to the death of patients. In this research, we designed and implemented a framework for the diagnosis of confusing diseases using Neutrosophic-Analytic Hierarchy Process (AHP) technique. The app was implemented using Java EE and MySQL database as the knowledge store; the objectoriented software engineering method used was employed in development.